A slender-body approach for computing second-order wave forces in seakeeping simulations of floating offshore wind turbines. - Carmo, Lucas Henrique Souza do (2021)
This thesis describes the development of METiS, a numerical tool for the seakeeping analysis of floating offshore wind turbines (FOWT). It is based on a slender-body approximation for evaluating the first- and second-order wave loads acting on a floating structure comprised of slender cylinders that combines Raineys equation, which can be seen as an extension of the inertial part of Morisons equation to include nonlinear terms, with Pinksters formulation for the low-frequency second-order loads on floating bodies. This combination is followed to allow the evaluation of the forces considering the mean body position, in such a way that an Inverse Fast Fourier Transform algorithm can be used to efficiently compute the time series of wave kinematics and second-order wave loads in a real sea condition directly in time domain, as opposed to the most common procedure of solving the second-order radiation/diffraction problem in frequency domain and importing the results to time-domain solvers. As a drawback of the approximation, end effects due to the extremities of the cylinder and effects due to wave scattering and radiation are lost, which is acceptable as long as the diameters of the cylinders that compose the structure are small in face of their draft and in face of the length of the incoming waves. These conditions may be too restrictive to modern oil & gas spars and semi-submersibles, which have large diameter columns, but it is satisfied by FOWTs in many significant wave conditions. The slender-body approximation is first verified by analyzing the simple case of a single surface piercing cylinder under the action of bichromatic waves, both bottom mounted and floating, for different combinations of the dimensionless parameters that describe the problem. The results are compared with the ones obtained with diffraction theory and Newmans approximation, evidencing an interesting complementarity between the two approximations and the conditions in which each of them performs the better. The relevance of the second-order terms from Raineys formulation is shown, demonstrating that the common practice of analyzing second-order loads by simply applying Morisons equation with second-order wave kinematics is not strictly correct. The method is then applied to the analysis of a semi-submersible FOWT model, moored by three caternary lines, that was tested at the wave basin of the Numerical Offshore Tank of the University of São Paulo. Three sets of tests are presented: free decays of the moored model; forced oscillations of the hull; and motions under the action of waves (bichromatic, JONSWAP and white-noise) and wind. The results obtained with METiS are compared with the experiments and with WAMIT and OpenFAST, illustrating the capabilities and limitations of each software.